Implementasi Program Pemantauan Pertumbuhan Perkembangan dan Gangguan Tumbuh Kembang Anak di Badan Layanan Umum Daerah (BLUD) Puskesmas Timika (Studi Kasus TK Integral Al-Amiin II Hidayatullah) - Martintje Maria Hukubun; Suci Megawati; Tjitjik Rahaju; Ahmad Nizar Hilmi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The high prevalence of dual nutritional problems and stunting among young children in Mimika Regency poses a serious challenge that requires consistent preventive measures. As a strategic step, the government has implemented regulations through Minister of Health Regulation No. 66 of 2014. This study aims to describe and analyze the implementation of the child growth and development monitoring program at the Timika Public Health Center (BLUD Puskesmas), specifically through a case study at the Al-Amiin II Hidayatullah Integrated Kindergarten. The approach used is descriptive qualitative, employing George Edwards III’s policy implementation theory as the analytical framework, which encompasses four main variables. Data in this study were collected through interviews, observations, and documentation involving the community health center, the school, and parents. The results indicate that communication has been clear and real-time through the use of official letters and a WhatsApp group. Regarding resources, collaboration between medical staff and educators was optimal, although the data recording system remained manual. Meanwhile, the disposition aspect demonstrated a high commitment to service from the implementers, and the bureaucratic structure was clearly defined through flexible MoUs and SOPs. This study recommends implementing data digitization for long-term efficiency and providing more private examination rooms at schools.